Analisis Kerentanan Pekerja Perempuan dalam Budaya Patriarki: Studi Kasus Profesi Ladies Companion (LC) pada Industri KTV di Surabaya - Nanda, Ummi Lailatul Azizah Permata (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This research aims to analyze the vulnerability of female workers in a patriarchal culture, specifically Ladies Companions (LCs) in the Karaoke TV (KTV) industry in Surabaya. This research focuses on two research questions: (1) How do power relations operate between KTV management, customers, and LCs? (2) How do these power relations discipline and control the female body in this context? This research employs a qualitative approach to analyze the power relations within the industry, drawing on Michael Foucault's theory. Data was collected through literature reviews, in-depth interviews, and observation. The findings of this research are: (1) Female workers, or LCs, occupy a powerless position within the power relations. The management, as the employer, holds authority and power over its employees, compelling them to serve customers (mostly adult men). (2) The management commodifies the bodies and service capacity of LCs to serve, assist, and entertain customers. Customer demands include female assistants who are hospitable and attractive women wearing sexy outfits, representing the ideal image of an LC. Management has the authority to supply and exploit LCs to provide adult entertainment. This power relation extends beyond a typical business relationship and demonstrates that being an LC is a profession that is extremely vulnerable, unsafe, and degrading to women's dignity.